2012
DOI: 10.4028/www.scientific.net/msf.721.185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Increased RES Generation on Power Systems Dynamic Performance

Abstract: In this paper, the impact of high wind power and photovoltaics penetration on the dynamic behavior of an island power system like one operates in Crete is investigated. Several simulations were performed leading to the fact that it is possible to achieve higher level of renewable energy sources penetration without significant dynamic security problems, if power units spinning reserve exists and the corresponding control systems have a sufficiently fast response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…DRESs will gradually replace conventional SGs in the near future in order to reach the worldwide targets for reducing carbon emissions. Inevitably, as a side effect, this will lead to certain frequency stability issues, since those units are mostly converter-interfaced and provide inherently little (e.g., doubly fed induction machines) or no (e.g., photovoltaics) inertia to the system [26]. The particular issue has been examined in reference [27], where a power system simulation was conducted by the Western Electricity Coordinating Council of the USA for the case of high penetration of wind generation and fossil fuel generation withdrawal, leading to noticeable system frequency response degradation.…”
Section: Inertial Responsementioning
confidence: 99%
See 1 more Smart Citation
“…DRESs will gradually replace conventional SGs in the near future in order to reach the worldwide targets for reducing carbon emissions. Inevitably, as a side effect, this will lead to certain frequency stability issues, since those units are mostly converter-interfaced and provide inherently little (e.g., doubly fed induction machines) or no (e.g., photovoltaics) inertia to the system [26]. The particular issue has been examined in reference [27], where a power system simulation was conducted by the Western Electricity Coordinating Council of the USA for the case of high penetration of wind generation and fossil fuel generation withdrawal, leading to noticeable system frequency response degradation.…”
Section: Inertial Responsementioning
confidence: 99%
“…The particular feature, commonly known as virtual or synthetic inertia, has been proposed as a service in several cases. For instance, the simulations in reference [26] have shown that it is economically and technically possible for the wind plants to provide an emulated inertia resulting to an even better inertial response compared to the case with no wind plants connection. Additionally, there exist new types of variable-output DRESs with the ability of providing controllable virtual inertial response and/or primary frequency response.…”
Section: Inertial Responsementioning
confidence: 99%
“…However, the distribution system's unbalance condition may have an impact on the PV plants integrated therein, which may then have an impact on the PV system's effectiveness. Besides the change of the level irradiance, temperature, and tripping where the high PV penetration also affected the operation of the system which affects the system's stability in both the steady state and the transient due to their unique characteristics that set them apart from conventional generation sources [8].…”
Section: Introductionmentioning
confidence: 99%
“…The basic goal of a power distribution network is to reduce energy losses and improve the transmission process in order to deliver electric energy to the end consumers at the desired quality (THD reduction with <5% as per IEEE 519 standards) [21], efficiency, and reliability [22], [23]. Many scholars have recognized reactive power compensation as a well-known method for reducing power loss while also offering many benefits like PF correction, voltage stability, increased transmission and operating ability of the network lines and devices, and optimization of the voltage profile [24], [25].…”
Section: Introductionmentioning
confidence: 99%